The Legal Politics of Human Rights Defenders' Protection: Criticism of Criminalization Practices and the Path to Justice - Sholihin Bone; Rahayu; Ratna Herawati (Universitas Islam Negeri Raden Intan Lampung, 2026)
The long struggle of human rights defenders in Indonesia continues to be met with serious challenges that remain unresolved. This study examines the political practice of law in protecting human rights defenders by analyzing existing legal frameworks and their implementation. Normatively, Law No. 39 of 1999 on Human Rights provides guarantees through several provisions, including Articles 3(2), 4, 8, 29(1), 30, 71, and 72. However, these legal protections have not been effectively implemented in practice. Empirical findings reveal that human rights defenders continue to experience various forms of violations, such as intimidation, physical and psychological attacks, criminalization, and judicial harassment. These actions often occur when defenders advocate for justice, environmental protection, and the preservation of livelihoods. Although regulatory frameworks formally recognize protection, they remain insufficient without more specific and comprehensive legal instruments, such as a dedicated law on human rights defenders. This research employs a normative legal method, utilizing legislative, conceptual, and case approaches to identify the gap between legal ideals and empirical realities. The findings indicate that weak protection mechanisms are largely due to the state's limited role in strengthening legal institutions that favor human rights defenders. The absence of a specific legal framework, combined with a repressive legal culture, exacerbates defenders' vulnerability in Indonesia. The primary purpose of this study is to emphasize the need for legal-political reconstruction oriented toward substantive justice through stricter regulation and the internalization of human rights values in law enforcement practice